The impact of social media marketing (tiktok) and online customer reviews on product skincare purchase decisions - Putri Putri; Santi Oktavianti; Teuku Muhammad Haqiqi; Noprian Noprian; Vanesha Rahmania; Saudi Berlian (Indonesia Accounting Research Journal, 2025)
This study examines the impact of TikTok-based social media marketing and online customer reviews on skincare product purchase decisions, focusing on Skintific as a case study among university students in South Sumatra. Guided by the Theory of Planned Behavior (TPB), this research explores how exposure to digital content and peer reviews influences consumer trust and behavioral intentions. Using a quantitative method, data were collected from 50 respondents through purposive sampling. The analysis involved multiple linear regression, t-test, and F-test. The results reveal that both TikTok marketing and online reviews significantly and positively affect purchase decisions. Social media marketing on TikTok increases product visibility and engagement, while online reviews enhance credibility and reduce perceived risk. Together, these variables explain 47.4% of the variation in purchase decisions. These findings emphasize the strategic importance of digital engagement and user-generated content in influencing consumer behavior in the skincare industry. The study offers insights for marketers seeking to leverage social media platforms to drive purchasing intent, particularly among younger demographics. Future research may explore additional influencing factors such as influencer credibility, product quality, and cross-platform effectiveness.